ANALISIS STRATEGI PEMASARAN DALAM PENJUALAN SAYUR PADA PEDAGANG KAKI LIMA DI PASAR INPRES KOTA PALU - Nur Azizah Maladjai; NurAfni NurAfni; Jane Fadilah; Aziz Ramadhan; Nuraisyah Nuraisyah; Andi Maman Firmansyah; Meldi Amijaya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research focuses on analyzing marketing strategies in selling vegetables to street vendors at the Inpres Market, Palu City. The aim of this research is to determine the marketing strategy for selling vegetables at the Inpres Market using Guiltinan and Paul's theory. This research method uses qualitative research, with interview and observation data collection techniques. The results show that (1) pricing strategies tend to be flexible using Guiltinan and Paul's theory. (2) Traders also focus on product quality and vegetable freshness to gain more trust from consumers. (3) traders take advantage of strategic locations in parking areas or exits, which allows consumers to reach them more easily. (4) using simple promotions such as direct communication with consumers, especially in the form of price offers and friendliness.